Single-cell image analysis reveals over-expression of organic anion transporting polypeptides (OATPs) in human glioblastoma tissue. Issue 1 (14th October 2022) - Cooper, Elizabeth; Woolf, Zoe; Swanson, Molly E V; Correia, Jason; Schweder, Patrick; Mee, Edward; Heppner, Peter; Turner, Clinton; Faull, Richard L M; Scotter, Emma L; Denny, William A; Choi, Peter J; et al.
Abstract: Background: Glioblastoma (GBM) is the most common and aggressive primary brain tumor in adults. Whilst the role of the efflux transporters are well established in GBM, the expression and function of uptake transporters, such as the organic anion transporting polypeptide (OATP) family, are not well understood. OATPs possess broad substrate specificity that includes anti-cancer agents; therefore, we sought to investigate the expression of four OATP isoforms in human GBM cell types using patient tumor tissue. Methods: We used fluorescent immunohistochemical labeling of paraffin-embedded surgically resected tissues and single-cell image analysis methods to explore the expression of the OATP isoforms in different tumor cell types through co-labeling with cell-type specific markers, such as IBA1 (pan-myeloid), GFAP (tumor cell), PDGFRβ (stromal cell), and UEA-1-lectin (endothelial). Results: We found significant over-expression of all the OATP isoforms (OATP1A2, 2B1, 1C1 and 4A1) in GBM tumor sections when compared to non-neoplastic brain. A single-cell image analysis revealed that OATPs were significantly upregulated throughout the tumor parenchyma, with significantly higher expression found on lectin-positive blood vessels and IBA1-positive myeloid cells in GBM compared to non-tumor brain tissue. Qualitative analysis of the four OATP isoforms demonstrated greater expression of OATP4A1 in peri-necrotic regions of GBM tissue, which correlated with hypoxia-related markers within the Ivy GAP RNAseq dataset. Conclusion: Here, we demonstrate, for the first time, the protein expression of four OATPs in human GBM tissue, including upregulation within the tumor microenvironment by myeloid cells and tumor vasculature, and isoform-specific upregulation within hypoxic niches.